A collaborative manufacturing execution system oriented to discrete manufacturing enterprises. (December 2016) - Wang, Huifen; Liu, Linyan; Fei, Yizheng; Liu, Tingting
The study aims to present architecture and technology solution for collaborative manufacturing execution system oriented to discrete manufacturing enterprises. Under the networked manufacturing environment, the enterprises are facing challenges including the increasing manufacturing process complexity, the shorter product delivery, the higher customer satisfaction requirements, and so on. To deal with these challenges, the manufacturing enterprises must implement information management, while collaborative manufacturing execution system is one of the key technologies to realize informationization. Thus, in this study, the authors analyze production characteristics, typical production flow, and collaborative management requirements of multi-workshop production in the discrete manufacturing enterprise and propose an architecture of collaborative manufacturing execution system oriented to discrete manufacturing enterprises. The main functions of this system and key technologies to realize the system is also analyzed. Finally, a prototype system is developed and a case study is executed in Henan Pingyuan Optics Electronics Co., LTD in OPTO-Electronic Group to demonstrate the implementation and potentials of the system.